Association between overactive bladder and pelvic organ mobility as evaluated by dynamic magnetic resonance imaging - Kurenai Kinno; Noritoshi Sekido; Yasuharu Takeuchi; Yoshitomo Sawada; Shoutarou Watanabe; Yasukuni Yoshimura (Scientific Reports, 2021)
Abstract Overactive bladder (OAB) is a prevalent condition, which negatively impacts patients’ quality of life. Pelvic organ prolapse (POP), also prevalent in women, has been recognized as an important etiology of female OAB, although the pathophysiological mechanisms remain controversial. In this study, we reviewed findings of dynamic magnetic resonance imaging (dMRI) in 118 patients with POP and investigated the association between dMRI findings, including positions and mobilities of pelvic organs as well as parameters of pelvic organ support and bladder outlet obstruction (urethral kinking), and OAB in order to elucidate the pathophysiology of OAB in patients with POP. Our results showed that compared with non-OAB patients, OAB patients had a significantly higher body mass index, more severe pelvic floor muscle impairment, and more profound supportive defects in the uterine cervix (apical compartment). On the other hand, dMRI parameters showed hardly any significant difference between patients with mild and moderate to severe OAB. These findings may imply that levator ani impairment and defective supports of the apical compartment could be associated with the presence of OAB and that the severity of OAB could be affected by factors other than those related to pelvic organ mobility and support or urethral kinking.